Opening the information industry marketplace : opportunities for Eastern Caribbean exports : final report (The Group ArlingtonUS, 1994)
Seeks to assist Eastern Caribbean countries in developing a strategy to attract telecommunications-sensitive business, especially in labour-intensive informatics export operations.
DC